DESKRIPSI PASAR TRADISIONAL DI KELURAHAN MENGGALA KOTA KECAMATAN MENGGALA KABUPATEN TULANG BAWANG - Mirna Octayani; Ali Imron; Iskandar Syah (FKIP UNIVERSITAS LAMPUNG, 2013)
The traditional market is a meeting place for sellers and buyers and on the mark with the building usually consists of stalls, stalls, and benthic nurseries open in the open by the seller as well as a market manager. The method used in this research is descriptive method. Data collection techniques, namely observation, and interviews. Data analysis techniques used are qualitative data analysis techniques. Based on the discussion results we concluded that Menggala Traditional markets have major commodities in the trade that fishermen catch fish around the river Menggala and Terasi Menggala already known by virtually the entire population of Lampung, besides the main commodity market transactions Menggala some are done in the boat as a means of in marketing merchandise. Differences with other traditional markets are looked at fish stalls that are found in the market as the main los.Kata kunci : pasar tradisional, menggala, tulang bawang